Contrasting approaches: the ozone layer, climate change, and resolving the Kyoto dilemma - Richard Elliot Benedick (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
In December 1997, after days and nights of bargaining that culminated two years of hard negotiations, representatives of 160 governments wearily agreed in Kyoto, Japan, on a protocol to supplement the 1992 United Nations Framework Convention on Climate Change. It was hoped that this “Kyoto Protocol” would represent a major step forward by the international community to mitigate emissions of greenhouse gases that could alter future climate. Before long, however, doubts emerged on whether the treaty was implementable, and even whether enough governments would ratify to allow its entry into force as international law. Nearly two years later (November 1999), a mere 16 nations – mostly small island states
Keywords: 300; had ratified. None were significant emitters of greenhouse gases.; Internationale Umweltpolitik; Umweltabkommen; Ozonschicht; Klimaschutz; Verhandlungen; Welt